"Father, Where Art Thou?" The Significance of Transgenerational Trauma in a Psychotherapy With Luke. (2nd October 2019) - Hargaden, Helena
Abstract: The author presents her work with a male client, choosing those parts of the clinical work that provide a context for the emergence of transgenerational trauma. She proposes that this type of trauma is encoded in multiple unconscious forms and only reveals itself through a nonlinear process requiring the therapist's disciplined and reflective use of her subjectivity. Using the theory of the domains of transference, she describes how previously traumatic self-states in both therapist and client are brought into conscious awareness. The theoretical focus is on episcript, epigenetics, and use of the therapist's subjectivity in the transformational transference as well as the use of symbolism, contemplation, and the discipline of hard reflection and thinking.